UPAYA PENINGKATAN PEMAHAMAN KONSEP FISIKA MELALUI IMPLEMENTASI TEORI BRUNER PADA SISWA MAN 2 BANDA ACEH - . Nurlaili (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2016)
The lack of the ability of students to understand the concept of teaching materials is influenced by several factors, including how teachers present it has not been improving student understanding and learning process has not been effective. This study aims to (1) determine the increase of student understanding, (2) the activities of teachers and students, (3) the ability of teachers to manage learning, and (4) students' response to the application of learning theory Bruner. The subjects were students of class X IPA3 the 2015/2016 school year was 26 students. This type of research is the Classroom Action Research (PTK) and the approach used in this research is descriptive statistical approach, the data is processed using statistics and narrated. Research data collection instruments that test, the observation sheet activities of teachers and students, observation sheet mengelolaan ability of teachers to learning, and pieces of students' response to PBM activities by using the theory of Bruner. Fourth test instruments analyzed using percentages. The results showed (1) an increase in activity of teachers and students during the learning process, (2) an increase in teachers' skills in managing the learning of the category is becoming a very good (3) the percentage of completeness individual as a whole increased from cycle 1 to cycle 3, namely 68% , 80% and 84%, and the percentage of the overall classical ketuntasanan also increased with 79%, 82% and 87%. (4) The students' responses tend to be positive where 97.33% of the students said he was happy to learning by using the theory of Bruner. From this study it can be concluded that the implementation of the theory of Bruner can enhance students' understanding on the material elasticity and Hooke's law.Keyword :Theoryof Bruner, understanding of concepts Kurangnya kemampuan siswa dalam memahami konsep materi ajar dipengaruhi oleh beberapa faktor diantaranya cara guru dalam menyampaikannya belum meningkatkan pemahaman siswa dan proses belajar mengajar belum efektif. Penelitian ini bertujuan untuk (1) mengetahui peningkatan pemahaman siswa, (2) aktivitas guru dan siswa, (3) kemampuan guru dalam mengelola pembelajaran, serta (4) respon siswa terhadap penerapan teori belajar Bruner. Subjek penelitian ini adalah siswa kelas X IPA3 tahun ajaran 2015/2016 yang berjumlah 26 siswa. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dan pendekatan yang digunakan dalam penelitian ini adalah pendekatan statistik deskriptif, data diolah menggunakan statistik dan dinarasikan. Instrumen pengumpulan data penelitian yaitu tes, lembar pengamatan aktivitas guru dan siswa, lembar pengamatan  kemampuan guru dalam mengelolaan pembelajaran, dan lembar respon siswa terhadap kegiatan PBM dengan menggunakan teori Bruner. Keempat instrumen dianalisis menggunakan uji persentase. Hasil penelitian menunjukkan (1) adanya peningkatan aktivitas guru dan siswa selama proses pembelajaran, (2) terjadi peningkatan keterampilan guru dalam mengelola pembelajaran dari kategori sedang menjadi sangat baik (3) persentase ketuntasan individual secara keseluruhan meningkat dari siklus 1 sampai siklus 3 yaitu 68%, 80%, dan 84%, dan persentase ketuntasanan klasikal secara keseluruhan juga meningkat yaitu 79%, 82%, dan 87%. (4) respon siswa cenderung positif dimana 97,33% siswa menyatakan senang terhadap pembelajaran dengan menggunakan teori Bruner. Dari penelitian ini dapat disimpulkan bahwa implementasi teori Bruner dapat meningkatkan pemahaman siswa pada materi elastisitas dan hukum Hooke.Kata kunci : Teori Bruner, Pemahaman Konsep